2016
DOI: 10.1177/0034355215610068
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Influence of Treatment Participation Rate on Post-Treatment Employment

Abstract: This study explored treatment participation rate as a mediator between individuals' baseline alcohol use, drug use, and psychiatric issue levels and post-treatment employment status. The study sample included 106 unemployed or underemployed individuals with substance use disorders who were participants in an intensive drug abuse treatment program. Structural equation modeling was applied to examine relationships between study variables. The results showed that (a) the direct effect of individuals' baseline alc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 79 publications
(118 reference statements)
0
1
0
Order By: Relevance
“…Research has shown that clients who experience substance use disorders have better employment-related outcomes when they participate in treatment for lengthier durations, or when they complete treatment, altogether (Arria & TOPPS-II Interstate Cooperative Study Group, 2003; Dunigan et al, 2014; Kim, Leierer, Atherton, Toriello, & Sligar, 2015; Luchansky, Brown, Longhi, Stark, & Krupski, 2000; Sung & Chu, 2011). However, because in the general population Blacks, American Indians, and Latinos experience higher unemployment rates and lower wages than Whites, it is possible that racial/ethnic disparities in employment outcomes exist (Bureau of Labor Statistics, 2016; U.S.…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that clients who experience substance use disorders have better employment-related outcomes when they participate in treatment for lengthier durations, or when they complete treatment, altogether (Arria & TOPPS-II Interstate Cooperative Study Group, 2003; Dunigan et al, 2014; Kim, Leierer, Atherton, Toriello, & Sligar, 2015; Luchansky, Brown, Longhi, Stark, & Krupski, 2000; Sung & Chu, 2011). However, because in the general population Blacks, American Indians, and Latinos experience higher unemployment rates and lower wages than Whites, it is possible that racial/ethnic disparities in employment outcomes exist (Bureau of Labor Statistics, 2016; U.S.…”
Section: Introductionmentioning
confidence: 99%